2017
DOI: 10.1155/2017/3837506
|View full text |Cite
|
Sign up to set email alerts
|

Oil Extraction from “Morelos Rice” Bran: Kinetics and Raw Oil Stability

Abstract: “Morelos rice” is a variety of rice with certificate of denomination of origin. It is a large grain of opaque appearance and extra large size that is grown exclusively in Morelos state (Mexico). Thus, the quality and characteristics of its rice bran may affect the kinetic of the extraction process of its oil as well as its stability. Therefore, this work is oriented to determine the extraction kinetics of its oil and its oxidative stability. The latter one is obtained through the proposal of a method based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
8
14
0
Order By: Relevance
“…In both cases, the plateaus correspond to the saturation of the deionized water due to both CO 2 and O 2 absorption and the oxidation products dissolution, respectively. Then, the interception of the tangent of the first plateau with the tangent of the second slope corresponds to the stability time of the biodiesel [41]. According to this, it can be observed that the oxidative stability of biodiesel was 23.6, 16.2, and 7.3 hours at 80, 110, and 140 ∘ C, respectively.…”
Section: Biodiesel Oxidative Stabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…In both cases, the plateaus correspond to the saturation of the deionized water due to both CO 2 and O 2 absorption and the oxidation products dissolution, respectively. Then, the interception of the tangent of the first plateau with the tangent of the second slope corresponds to the stability time of the biodiesel [41]. According to this, it can be observed that the oxidative stability of biodiesel was 23.6, 16.2, and 7.3 hours at 80, 110, and 140 ∘ C, respectively.…”
Section: Biodiesel Oxidative Stabilitymentioning
confidence: 78%
“…Moisture (water) tends to condense on the metal surfaces that contain it and causes their deterioration due to metallic corrosion. In addition, the reaction products of the biodiesel oxidation process (aldehydes, ketones, lactones, and organic acid compounds) considerably increase the biodiesel's corrosivity [41,47]. The corrosivity of biodiesel on different metallic materials has been evaluated both by electrochemical techniques and by mass loss tests.…”
Section: Biodiesel Corrosivitymentioning
confidence: 99%
“…The FTIR spectrum analysis showed the main characteristic signals, such as: a peak at 3007 cm −1 attributed to the stretching vibration of cis -olefin double bonds (=C–H), an asymmetric stretch band of methylene at 2925 cm −1 , a symmetric stretch band of methylene at 2854 cm −1 , the band corresponding to the group C=O of the triglycerides at 1746 cm −1 , the band corresponding to the group CH 2 at 1462 cm −1 , and the stretch corresponding to –COO at 1163 cm −1 . This was in addition to other signals, such as the one at 723 cm −1 due to the overlap of the methylene equilibrium vibration, and the flexural vibration outside the plane of the cis -disubstituted olefins (HC=CH–) [34,35,36,37].…”
Section: Resultsmentioning
confidence: 94%
“…The control oleogel (CR1) showed a sharp signal at 3005 cm −1 in the spectrum, which can be attributed to the stretching vibration of cis olefinic double bonds (=C–H) [ 47 ]. The peaks obtained at 2922 cm −1 and 2852 cm −1 were due to the asymmetrical and symmetrical stretching vibration of methylene (–CH 2 ) groups in the fatty acid molecules [ 47 ]. The carbonyl (–C=O) stretching vibration of the ester bond was evident from the peak observed at 1742 cm −1 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%